Effect of Different Pig Fecal Microbiota Transplantation on Mice Intestinal Function and Microbiota Changes During Cold Exposure - Liu, Ting; Guo, Yanbo; Lu, Chang; Cai, Chunbo; Gao, Pengfei; Cao, Guoqing; Li, Bugao; Guo, Xiaohong; Yang, Yang (Frontiers in Veterinary Science, 2022)
Cold stress influences intestinal processes, causing physiological and immunological responses in animals. Intestinal microbiota participates in maintaining the stability of the intestinal environment. However, phenotypic characteristics and the effects of porcine microbiota changes under cold conditions remain poorly understood. Here, the fecal microbiota of cold tolerant breed (Mashen) and cold sensitive breed (Duroc-Landrace-Yorkshire) were transferred to germ-free mice respectively. After a cold exposure (4 ℃) for 21 days, intestinal function and microbe changes of mice were explored. The results showed that Mashen pigs microbiota transplantation made the body temperature of the mice stable, in which the fat weight and expression of Ucp1, Cpt1b and Pgc-1α were significantly higher (P<0.05) than those of the control group. The results of intestinal structure and expression of serum inflammatory factors showed fecal microbiota transplantation (FMT) mice have more intact intestinal structure and high expression of proinflammatory factor such as IL-4. The study of mice fecal microbiome characterised via 16S rRNA sequencing found that pig microbiota transplantation changed the abundance of Firmicutes. In addition, it identified discriminative features of Firmicutes in the microbiota between two breeds of pig, in which Clostridiaceae were enriched in the microbiota community of Mashen pig, and Coriobacteriales were significantly (P<0.05) enriched in Duroc-Landrace-Yorkshire pig microbiota transplantation group based on LEfSe analysis. Finally, we found that the content of propionic acid and butyric acid in rectal contents significantly changed, and the abundances of Clostridium and Lachnspira showed significant correlations with changes in short-chain fatty acids. The results suggest that pig fecal microbiota transplantation can alleviate the changes in physiological and biochemical indicators in mice caused by cold exposure. The fecal microbiome of Mashen pigs possible be more beneficial for mice during cold exposure.